Traditional Games and Traditional Sports Boalemo - Hartono Hadjarati; Arief Ibnu Haryanto (IKIP Budi Utomo Malang, 2021)
This study aims to survey traditional games in Boalemo Regency, Gorontalo Province. This research is a qualitative research with the main procedure involving purposeful sampling with research subjects namely children, students, local government and local traditional leaders. The results of this study show that there are several types of traditional games in Boalemo Regency, namely Pa'I, Neka, Redi, Cur-cur Pal, Tera, Palapudu, Moyo, Tenggedi Lo Buawu, Alanggaya Molo'u, Pohayato Lo Dungo Tangi Lo Bindalo, Kura -kura, Tenggedi Lo Wawohu, Wayang Buang-Buang, Puppet Poko-Poko, Kuti-kuti, Use, Ponti, Jump Rope. Meanwhile, traditional game sports in Boalemo Regency, Gorontalo Province, namely Langga. The conclusion is that there are eighteen traditional games and one traditional sport in Boalemo Regency.